Virtual Reality And Ambisonics As Effective Combination Of Immersive Media In Raising Awareness For Indonesia’s Birds Conservation Organization - Arya Harditya; Tombak Matahari (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2021)
Virtual Reality arguably has been one of the most popular immersion media for many years, especially 360 Video Camera, but its utilization is only limited to entertainment purposes, thus this research would like to test wider potentials outside its evident field of interest. On the other hand, audio has always been the forgotten elements in many audio-visual productions because its intangibility, this research will explore one of many emerging audio sciences, which is Ambisonics / 3D Spatial Audio. By combining the two powerful elements, this research is trying to prove the user engagement and communication strategy’s effectivity especially in raising awareness for Indonesia’s bird’s conservation NGO called Burung Indonesia, where the 360 Video Camera captures the environment and 3D Spatial Audio captures the sound of Indonesia’s birdlife. Therefore, the output of this research is to discover new communication infrastructure through digital fabrication.